Weryfikacja modelu stateczności drzew na terenach zalewowych na przykładzie dębu Quercus robur L., sosny Pinus sylvestris L. i olchy Alnus glutinosa (L.) Gaertn. - Kałuża, Tomasz (Leśne Prace Badawcze, 2012)
A tree’s geometrical characteristics (diameter, trunk height, vertical and horizontal extent of roots) and the soil’s geotechnical properties (type and state of soil) determine the critical force required to cause uprooting. This article presents a method for the estimation of the critical force causing uprooting of a tree during high winds and flooding in riparian forests. The model was tested for forest stands of black alder, Scots pine and pedunculate oak. The force required to pull up various trees was measured, and results used as the basis for formulation and verification of a theoretical model describing the critical threshold value for uprooting.